2001
DOI: 10.1128/mcb.21.14.4470-4481.2001
|View full text |Cite
|
Sign up to set email alerts
|

PLIP, a Novel Splice Variant of Tip60, Interacts with Group IV Cytosolic Phospholipase A2, Induces Apoptosis, and Potentiates Prostaglandin Production

Abstract: The group IV cytosolic phospholipase A 2 (cPLA 2 ) has been localized to the nucleus (M. R. Sierra-Honigmann, J. R. Bradley, and J. S. Pober, Lab. Investig. 74:684-695, 1996) and is known to translocate from the cytosolic compartment to the nuclear membrane (S. Glover, M.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 75 publications
2
50
0
1
Order By: Relevance
“…Subsequently, full-length Tip60 has been found in association with membrane-bound receptors in a study that verified both nuclear and cytoplasmic expression (Sliva et al, 1999). Recent studies suggest that Tip60 shuttles between the cytoplasm and the nucleus in response to stimuli such as endothelins (Lee et al, 2001) and serum starvation (Sheridan et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, full-length Tip60 has been found in association with membrane-bound receptors in a study that verified both nuclear and cytoplasmic expression (Sliva et al, 1999). Recent studies suggest that Tip60 shuttles between the cytoplasm and the nucleus in response to stimuli such as endothelins (Lee et al, 2001) and serum starvation (Sheridan et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Second, cPLA 2 -interacting protein (PLIP), a splice variant of Tip60, interacts with the N-terminal region of cPLA 2 a. 72) In renal mesangial cells, cPLA 2 a colocalizes with PLIP in the nucleus. Despite this unusual cPLA 2 a localization, overexpression of PLIP potentiates cPLA 2 a-mediated PGE 2 production and serum deprivationassociated apoptosis.…”
Section: -5 Regulation By Protein Interaction and Cleavagementioning
confidence: 99%
“…The NuA4 complex itself is broadly conserved (Doyon and Côté, 2004) and the human catalytic subunit Tip60 functions in nontranscriptional components of apoptosis and signaling processes (Ikura et al, 2000;Sheridan et al, 2001). Tip60 has been linked to DNA repair (Ikura et al, 2000) and a role for Esa1p and the Yng2p NuA4 subunit was found in replication-coupled DNA double-stranded break repair (Bird et al, 2002;Choy and Kron, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Esa1p is the catalytic component of the 1.4-MDa NuA4 HAT complex that is important for transcriptional activation both in vitro and in vivo at specific target loci, including many ribosomal protein genes (reviewed in Doyon and Côté, 2004). Esa1p also functions in the highly active, smaller picNuA4 complex (Boudreault et al, 2003).The NuA4 complex itself is broadly conserved (Doyon and Côté, 2004) and the human catalytic subunit Tip60 functions in nontranscriptional components of apoptosis and signaling processes (Ikura et al, 2000;Sheridan et al, 2001). Tip60 has been linked to DNA repair (Ikura et al, 2000) and a role for Esa1p and the Yng2p NuA4 subunit was found in replication-coupled DNA double-stranded break repair (Bird et al, 2002;Choy and Kron, 2002).…”
mentioning
confidence: 99%